Re-evaluating merit: Multiple overlapping factors explain the evolution of numerical notations. Issue 1 (2nd January 2017) - Chrisomalis, Stephen
ABSTRACT: How should we evaluate the merit of written numeral systems? The present ubiquity of the Hindu-Arabic (Western) numerals might suggest that narrow considerations of efficiency have promoted the convergence of numerical traditions on a single, superior solution. Comparing the historical evolution of numerical notations to the history of writing systems suggests, instead, that a host of social factors influence the adoption, transmission, retention and replacement of numeral systems. The wide range of contextual uses and functions of written numerals belie any simple explanation of the choices underlying their abandonment. Following the criteria outlined by Coulmas, a sociolinguistic model is proposed in which a wide variety of technical, graphic and cultural factors must be considered in order to fully explain the historical record.